Introduction - Arkesteijn, Monique (A+BE | Architecture and the Built Environment, 2019)
Corporate Real Estate Corporate real estate is real estate that is necessary for an organization to conduct its business. CRE can be owned or leased space and is different than commercial real estate. CoreNet Global (2015) describes that in commercial real estate, real estate is core business, and the goal is to provide a risk adjusted return to the investor; whereas, in corporate real estate, real estate supports the business function. Corporate real estate represents the demand side or user side of real estate, while commercial real estate focuses on the supply side to meet that demand. CRE function lacks tools to deliver the most business impact Sharp (2013) concluded based on 636 survey responses that CRE teams face barriers to meet present challenges. The barriers are “C-suite resistance to capital expenditure; the sometimes small and fragmented structure of the CRE function; inadequate access to deep data and analytics to measure value; and a fundamental skill and knowledge gap within CRE teams ... . Furthermore, many CRE departments lack the tools and training to effectively identify, shape and execute the broader business strategies that would ultimately deliver the most business impact. Only 28 percent regard themselves as ‘well equipped’ to meet the various tactical and strategic demands now being placed upon them” (Sharp, 2013, pp. 232-233). What if CRE departments were better equipped ... with an approach that enables them to choose the best CRE strategy and portfolio design that adds most value to all stakeholders in the organization?